Book art : creative ideas to transform your books decorations, stationery, display scenes, and more - Youngs, Clare (London ; New York : Cico Books, 2012)
Book Art has 35 innovative designs to transform your books from their original purpose into something attractive and inspiring. Do you have a shelf of old books that you love, but rarely touch? Well why not give them a new lease of life and use them to create one of the 35 beautiful projects Clare Youngs has developed? Divided into five chapters, you will discover ways to make greetings cards, stationery, animals, display scenes and more using pages from all kinds of different books. The beautiful typography and vintage style artworks will provide interesting colour, pattern and texture to designs such as the owl and pussycat pop up scene. The illustrations in children's books give a vintage feel to bunting or an alphabet to decorate a kid's room, while maps and atlases work well on lampshades or birthday cards. Use elegant images from interiors books to decorate a wardrobe and chest of drawers or cut away at a hardcover book to make displays like the cliff and lighthouse scene. The designs use a variety of crafting techniques, from quilling to collage and diecutting, and each project comes with easy to follow instructions and step by step artworks. There's also a helpful techniques section at the back that will be of real use to first-time crafters, handy time saving tips that more confident crafters will appreciate and a templates section.
Includes index.
Keywords: Paper work; Handicraft; Waste paper -- Recycling